Spectroscopic Study the Air-Processed Degradation Mechanism of Inverted Organic Solar Cells - Wang, Minshuai; Cai, Xiaomei; Huang, Yinghong; Zheng, Kai; Li, Fumin (Frontiers in Physics, 2020)
Organic solar cells are promising for the next-generation photovoltaic technology owing to its low cost and flexibility. The possibility of efficient large-area roll-to-roll production has attracted worldwide industrial interest. However, the instability and glove-box process still impede the industrial production of organic solar cells. In this paper, we investigated air-processed degradation mechanisms to provide instructions for practical applications. The air-processed degradation mechanism of the organic solar cells is ascribed that the PEDOT:PSS interfacial layer is oxidized by oxygen and the active layer p-DTS(FBTTh2)2 tends to be affected by water. The air-processed degradation of the PEDOT:PSS interfacial layer results from the oxidation and desulfurization of PEDOT:PSS, which caused huge efficiency loss. The active layer of p-DTS(FBTTh2)2:PC71BM tends to be affected by ambient environment, which led to fatal results. The research on these unresolved degradation mechanisms enables us to choose the suitable materials and get stable performance in the air-processed situation.